دور الاعلام المدرسي في تصحيح رغبات سنة رابعة متوسط وفق ملمحهم دراسة ميدانية بمتوسطة البشهيد بلهوشات بوزيد تاجموت الاغواط - بن صحراوي زين العابدين; برق طاهر; جلالي ناصر (My University, 2023)
School media is a continuous and purposeful educational activity with the aim of strengthening the student’s knowledge of everything related to school and professional life, in order to integrate him with the various educational, social and economic requirements and help him to acquire skills and competencies that contribute to the development of his inclinations and the development of his interests to form his choices and formulate study perceptions within a study project that is compatible with his abilities, ambitions and horizons Ruler for different disciplines and study paths. From here came the idea of the study, which aimed to know the effectiveness of school media in correcting students’ desires according to their academic profile and its contribution to urging students to self-inquiry about academic paths and specializations, and to what level the degree of influence expected from school media can vary based on the different academic specialization . This study was conducted in the middle school of Belhouchat Bouzid, municipality of Tajmot, Laghouat province, and the descriptive exploratory method was used in this study. The sample of the study was 7 students out of 70 students. We also used the Desire Card as a tool for data collection.